Charakter siły roboczej w gospodarce socjalistycznej - Obrębski, Tadeusz (Wydział Prawa i Administracji UAM, 1977)
In the paper an attempt was made to analyse labour force as an economic category of socialist economy which is still causing controversy. The purpose of the paper is: first to explain the contents of the economic form of the labour force, second to analyse the views on the nature of the labour force, third to define that labour force economy is conditioned by its concrete economic form. Three kinds of views on the nature of the labour force were analysed: first according to which labour force has value and hired character, second according to which labour force is not an article of trade, has no value but is subject to hiring, and third according to which labour force is not an article of trade, has no value and hired character. On the basis of the analysis, the thesis was formulated (that the most consequent and most fully taking (into account the essence and nature of socialist economic relations is the third view according to which labour force is not an article of trade, has no value and is not subject to hiring.
Characteristic of Labour Force in the Socialist Economy